2021
DOI: 10.1111/1471-0528.16771
|View full text |Cite
|
Sign up to set email alerts
|

Patient experience of telephone consultations in gynaecology: a service evaluation

Abstract: Objective To investigate patient perspective of telephone consultations (TCs) in gynaecology and identify which patients benefit most from a telemedicine system. Design Service evaluation.Setting Gynaecology outpatient services at a tertiary referral hospital.Population Patients who received a TC during May and June 2020.Methods Postal questionnaire combining three validated tools: QQ-10, Patient Enablement Index (PEI) and National Health Service Friends and Family Test (NHS-FFT). Quantitative data and free te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 27 publications
4
13
0
Order By: Relevance
“…Consistent with other studies of gynaecological services, this study adds to the evidence that telehealth is acceptable and satisfactory to women with many preferring to receive aspects of their care via telehealth, rather than face‐to‐face consultations 4,8,10,21,22 . The benefits of telehealth as reported here, include improved flexibility, access and convenience, reduced personal costs (lost wages, travel and parking fees), safety and perceived equivalent care quality had they attended face‐to‐face 5,8,21 . Virtual attendance also limited disruptions to women's work, family and social life 21,23 …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Consistent with other studies of gynaecological services, this study adds to the evidence that telehealth is acceptable and satisfactory to women with many preferring to receive aspects of their care via telehealth, rather than face‐to‐face consultations 4,8,10,21,22 . The benefits of telehealth as reported here, include improved flexibility, access and convenience, reduced personal costs (lost wages, travel and parking fees), safety and perceived equivalent care quality had they attended face‐to‐face 5,8,21 . Virtual attendance also limited disruptions to women's work, family and social life 21,23 …”
Section: Discussionsupporting
confidence: 83%
“…2,3 Reported benefits of telehealth include improved access to care, increased convenience, reduced travel burden and improved patient satisfaction. [4][5][6] However, barriers to telehealth have been reported including difficulties building rapport between patients and clinicians, inability for physical examination, funding constraints, lack of privacy, inadequate healthcare infrastructure and processes, hearing difficulties and technology challenges. [4][5][6] Monash Health, the largest Australian public health service, provided over 1.5 million episodes of tertiary outpatient care in 2019-2020.…”
Section: Introductionmentioning
confidence: 99%
“…Telehealth has already been shown to have many specific applications in gynaecology including: contraceptive advice, 14 vulvovaginitis, 15 pre‐ and post‐surgical care, 16 urogynaecology, 17 fertility, 18 medical termination of pregnancy, 19 and management of sexually transmitted infections. 20 Furthermore, Khan et al 21 recently found that telephone consultations in gynaecology are convenient and effective. This study further adds to the evidence that telehealth is acceptable for managing patients with a range of presentations in a general gynaecology outpatient setting.…”
Section: Discussionmentioning
confidence: 99%
“…Patients received surveys 3 to 9 weeks post-consultation, depending upon whether their appointment was at the start or the end of the sample time frame. Data from urogynaecology TCs were extracted from the responses to the service evaluation investigating experience of TC across all gynaecological sub-specialities [ 16 ]. Clinical outcome data were obtained from electronic patient records for all urogynaecology patients who attended TCs May to June 2020.…”
Section: Methodsmentioning
confidence: 99%